Orchestrating coordination among humanitarian organizations - Ruesch, Lea; Tarakci, Murat; Besiou, Maria; Van Quaquebeke, Niels (Production and Operations Management, 2022)
Disasters mobilize hundreds of organizations, but coordination among them remains a challenge. This is why the United Nations has formed clusters to facilitate information and resource exchange among humanitarian organizations. Yet, coordination failures in prior disasters raise questions as to the effectiveness of the cluster approach in coordinating relief efforts. To better understand barriers to coordination, we developed a grounded theory and augmented the theory with an agent‐based simulation. Our theory discerns a cluster lead's roles of facilitating coordination, but also investing in its own ground operations. We find that specifically serving such a dual role impairs swift trust and consequent coordination among cluster members. The additional simulation findings generalize the detrimental effect of the cluster lead's dual role versus a pure facilitator role and specify it against various boundary conditions.